A biochemical study of berry abscission in Waltham Cross grapes - Wolf, E. E. H.(Erhard Erwin Herbert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1991.